On An Improved Parallel Construction Of Suffix Arrays For Low Bandwidth Pc-Cluster. - Kok, Jun Lee; Abdul Rashid, Nur'Aini; Abdullah, Rosni; Md. Ali, Norhashidah (2003)

(untitled)
An algorithm for the parallel construction of suffix arrays generation for any texts with larger alphabet size on distributed memory architecture is presented